PENERAPAN MODEL DIRECT INSTRUCTION DALAM PEMBELAJARAN OLAHRAGA PATANQUE - Saharuddin Ita; Wiwit Wiwit; M. FP. Putra (JURNAL PENGABDIAN PAPUA, 2017)
Petanque is new sport, specially in Papua-Indonesia. Because of new sport so many student can not right play of petanque sport. Giving training with model of Direct Instruction (DI) can be solution to solve the problem in field. Sport action was taked as method of service. The find out of the service was (1) training with model of direct instruction increasing learning achievement student of petanque sport, (2) training with model of direct instruction increasing learning achievement university student of petanque sport.Keywords: direct instruction, petanque sport, Papua